2023
DOI: 10.1039/d3gc02118a
|View full text |Cite
|
Sign up to set email alerts
|

From screening to the hectogram scale: sustainable electrochemical synthesis of mefenpyr-diethyl

Abstract: To demonstrate the technical application potential of electrochemical reactions, we developed a synthetic method to access commercially available herbicide safener mefenpyr-diethyl. In a simple undivided electrolysis cell with non-hazardous aqueous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Mechanistic Considerations. Based on the described findings and in accordance to previous reports, 28,33,39,49 the following mechanism is proposed (Scheme 6): Similar to the mechanism described by Shono et al, 28 iodide is, in a first step, anodically oxidized to triiodide in the aqueous layer. At the phase boundary, oxime 5 is then oxidized by triiodide in analogy to the mechanism for the oxidation of oximes with NCS proposed by Togo and Kobayashi.…”
Section: Optimization Of the Electrolytic Conditionssupporting
confidence: 85%
See 1 more Smart Citation
“…Mechanistic Considerations. Based on the described findings and in accordance to previous reports, 28,33,39,49 the following mechanism is proposed (Scheme 6): Similar to the mechanism described by Shono et al, 28 iodide is, in a first step, anodically oxidized to triiodide in the aqueous layer. At the phase boundary, oxime 5 is then oxidized by triiodide in analogy to the mechanism for the oxidation of oximes with NCS proposed by Togo and Kobayashi.…”
Section: Optimization Of the Electrolytic Conditionssupporting
confidence: 85%
“…The envisioned setup was based on methods for the electro-organic synthesis of pyrazolines and pyrazoles published by Waldvogel et al ,, Starting from the reported conditions for the pyrazoline synthesis from glyoxylate hydrazones, a transfer on the conversion of ethyl 2-(hydroxyimino)­acetate (Scheme , 5b ) and the reaction of the corresponding nitrile oxide with styrene was attempted. The appropriate supporting electrolyte, electrode material, and solvent were tested first (see Table S4).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Waldvogel, in collaboration with Bayer, reported the synthesis of the herbicide mefenpyr-diethyl from 2,4-dichlorophenylhydrazone hydrochloride via electrolysis of either (Z)-hydrazone 39 or (E)-hydrazone 40 and methacrylate to afford 41 (Scheme 16). 121 The oxidation was achieved using a 1.5 L jacketed glass vessel equipped with six graphite electrodes and aqueous sodium iodide, which serves as both the supporting electrolyte and the mediator. The oxidative cyclization was done on 209 g of 39 and 42 g of 40, achieving comparable yields of 66% and 63% yield, respectively.…”
Section: ■ Oxidationsmentioning
confidence: 99%
“…The commercial herbicide safener mefenpyr-diethyl synthesis was presented as a highlight for this elegant and scalable protocol, allowing hectogram quantities. [64] A different iodide-mediated protocol was reported for the electrochemical synthesis of aziridines via the NÀ H bond activation (Scheme 18c). [65] With potassium iodide as a mediator role, external oxidants are avoided, and the reaction is complimented by the cathodic evolution of hydrogen as the byproduct.…”
Section: Category G (Halide Mediation)mentioning
confidence: 99%